The Effectiveness of Gadgets in Enhancing Teenagers’ Understanding of Islamic Teachings in Besar II Terjun Village - Sari, Della Patika; Zulkarnain, Zulkarnain (Journal of Islamic Thought and Philosophy, 2025)
This study aims to analyze the influence of gadget use on the understanding of Islamic teachings among adolescents in Besar II Terjun Village, Pantai Cermin District, Serdang Bedagai Regency. The research subjects included adolescent gadget users who access religious content through various digital platforms. However, the question then arises: are gadgets effective in helping adolescents understand Islamic teachings in today's era? This study was conducted in Besar II Terjun Village, Pantai Cermin District, Serdang Bedagai Regency, to see how gadgets can improve adolescents' understanding. A quantitative approach was used by collecting data through questionnaires and analyzing the relationship between variables using a correlation test. The results showed a positive correlation of 0.595 between gadget use and understanding of Islamic teachings, with a p-value <0.001 (sig <0.05). This finding indicates that gadget use has a significant contribution in improving adolescents' understanding of Islamic teachings.